Effects of unsaturated fatty acids, lipid oxidation, myoglobin, and hemoglobin on livery flavor volatiles in beef steaks - Yancey, E.J.; Dikeman, Michael E.; Smith, J. Scott; Hachmeister, K.A.; Chambers, Edgar, IV; Gadgil, P.; Milliken, George A.; Dressler, E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Infraspinatus (top blade), gluteus medius (top sirloin), and psoas major (tenderloin) steaks were obtained from A- and B-maturity carcasses that had either a high (≥ 6.0) or normal (≤ 5.7) pH, and either slight or small marbling. The steaks were vacuum aged until either 7, 14, 21, or 35 days postmortem. The steaks were broiled and served to a highly trained flavor-profile sensory panel. Steaks with livery flavor were subjected to gas chromatography/mass spectrometry analyses for flavor compounds. Steaks aged until 7 or 35 days postmortem were analyzed for the 2- thiobarbituric acid reactive substances (TBARS) content to determine lipid oxidation and for myoglobin and hemoglobin concentrations. Thirteen different volatile compounds had greater amounts in steaks with livery flavor. Lipid oxidation of raw steaks was not related to livery flavor, but steak myoglobin concentration was related to livery flavor.
Keywords: Beef; Unsaturated fatty acids; Lipid oxidation; Myoglobin; Hemoglobin